ANALISIS RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN RITEL YANG TERDAFTAR DI BEI PERIODE 2013-2019 - Nicolas Williem; Gracia S Ugut (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
Financial distress is a condition where a company is having difficulties to pay its liabilities. Retail companies are companies that are exposed to financial distress on 2013-2019 period shown by low or negative net income growth. The purpose of this research is to analyze financial ratios, such as profitability ratio, consists of net profit margin and gross profit margin, liquidity ratio, leverage ratio which consists of long term debt to equity ratio, and activity ratio which consists of inventory turnover, to dependent variable financial distress, with Altman Z-Score method. The results of this research shows that profitability ratio that consists of net profit margin and gross profit margin, liquidity ratio, is significant to financial distress. Leverage ratio and inventory turnover doesn’t have significant effect to financial distress.